Investigation of tool wear and surface integrity on MQL machining of Ti-6AL-4V using biodegradable oil - Rahim, E. A.; Sasahara, H (SAGE Publication, 2011)
Minimum quantity lubrication (MQL) machining involves the application of small quantity of lubricant to the tool–workpiece interface. This paper describes the results of an investigation on the effects of using different MQL lubricants (synthetic ester and palm oil) on the drilling of Ti-6Al-4V. Dry cutting was also performed for comparison purposes. It was found that drilling under dry conditions resulted in the shortest tool life due to severe chipping. MQL is beneficial to the measured responses such as tool life, thrust force, torque, and temperature. The outstanding performance of palm oil in reducing the value of those responses was attributed to its ability to form a thin film which promoted boundary lubrication during the machining process. The presented results indicated the substantial benefit of using palm oil in terms of microhardness, surface roughness, and subsurface deformation. This work shows that palm oil can be used as a viable alternative to a synthetic ester as a MQL lubricant.